URBAN HERITAGE REVITALIZATION THROUGH POTENTIAL OPTIMIZATION OF BUFFER ZONE IN GRESIK - Utami, Adinda Sih P R; Nasution, Tanti Santriana Rosary; Santosa, Satya Wahyuputra (Border: Jurnal Arsitektur, 2019)
Conservation of cultural heritage area in Gresik has been implemented since 2009. The conservation process includes documentation, classification, and physical improvement. However, damage, change, and quality degradation in heritage area are still occurred. One of revitalized area in Gresik is Kampung Kemasan. The phenomena that emerge today is that the revitalization in Kampung Kemasan is deemed inadequate either to trigger the revival of heritage area in larger scale or to avoid the quality degradation of its surrounding heritage area. Therefore, this research aimed to find a solution of this problem by proposing design that focused on development of Kampung Kemasan buffer zone. This study used a qualitative descriptive method. Data were collected through community participation in order to mapping the region's potential, observation, and spatial interpreting. The spatial interpreting in this case is the interpretation of the character space formed in buffer zone. After all the data was obtained, it was analyzed by using the overlay method to obtain spaces that would be planned further. Results of the research are a buffer zone planning with design intervention on street furniture and pedestrian way that reinforces the image or the theme of the cultural heritage area.